Determinants of real water losses in the Australian drinking water sector. Issue 8 (14th September 2019) - Ananda, Jayanath
ABSTRACT: The Sustainable Development Goals (SDG) agenda calls for safe drinking water and sanitation for all communities around the world and the use of water in a sustainable and efficient manner. Although under less scrutiny in developed countries, network water losses can be a costly resource misallocation. This paper analyses real water losses in drinking water networks in Australia by applying a panel data regression model with fixed effects to ascertain the main drivers of real water losses. The results indicate population growth and water main breaks as major drivers of water losses in Australia. Real water losses also have an impact on utilities net revenue per unit water delivered, infrastructure leakage index and operational costs. In order to reduce real water losses, water managers and regulators must pay more attention to the health of the distribution network in the face of rapid urbanisation experienced in the east coast of Australia.